Radiation Measurement with Data Acquisition Using LabVIEW - Tiyapun*, Kanokrat; Seemapapon, Sirirat; Hemla, Panya; Wetchagarun, Saensuk; Punnachaiya, Suvit; Keawmorakot, Udomsak (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Radiation monitoring and measurement are important for radiation safety. Such monitoring and measurement must be carried out in order to investigate workplace conditions and individual exposures, to ensure that radiological conditions in the workplace are acceptable, safe, and satisfactory, and to keep records of radiation monitoring over a long period of time in accordance with regulations or as good practice. However, radiation monitoring instruments and system are expensive. A cost-effective radiation monitoring system using Geiger Muller (GM) radiation detector was developed. A high voltage generation circuit and data acquisition were implemented using LabVIEW software. The cost-effective radiation monitoring system is easy to use, and it can detect radiation, analyzed and record the data in a personal computer. This newly developed system is simple and can provide the radiation dose data for further analysis. An experiment was conducted to compare and calibrate the collected data at the Secondary Standard Dosimetry Laboratory (SSDL). The result shows that the new developed GM detector provides good correlation between counts per minute (cpm) and dosage units, which is good characteristic of a radiation counting system. Keywords: GM counter; high voltage generation radiation detection; data acquisition *Corresponding author: Tel.: (+662) 4019889 Ext.5211 E-mail: kanokrat@tint.or.th